Beneficial role of overexpression of TFPI‐2 on tumour progression in human small cell lung cancer. Issue 1 (27th June 2013) - Lavergne, Marion; Jourdan, Marie-Lise; Blechet, Claire; Guyetant, Serge; Pape, Alain Le; Heuze-Vourc'h, Nathalie; Courty, Yves; Lerondel, Stephanie; Sobilo, Julien; Iochmann, Sophie; Reverdiau, Pascale
Abstract : Tissue factor pathway inhibitor‐2 (TFPI‐2) is a potent inhibitor of plasmin, a protease which is involved in tumour progression by activating (MMPs). This therefore makes TFPI‐2 a potential inhibitor of invasiveness and the development of metastases. In this study, low levels of TFPI‐2 expression were found in 65% of patients with small cell lung cancer (SCLC), the most aggressive type of lung cancer. To study the impact of TFPI‐2 in tumour progression, TFPI‐2 was overexpressed in NCI‐H209 SCLC cells which were orthotopically implanted in nude mice. Investigations showed that TFPI‐2 inhibited lung tumour growth. Such inhibition could be explained in vitro by a decrease in tumour cell viability, blockade of G1/S phase cell cycle transition and an increase in apoptosis shown in NCI‐H209 cells expressing TFPI‐2. We also demonstrated that TFPI‐2 upregulation in NCI‐H209 cells decreased MMP expression, particularly by downregulating MMP‐1 and MMP‐3. Moreover, TFPI‐2 inhibited phosphorylation of the MAPK signalling pathway proteins involved in the induction of MMP transcripts, among which MMP‐1 was predominant in SCLC tissues and was inversely expressed with TFPI‐2 in 35% of cases. These results suggest that downregulation of TFPI‐2 expression could favour the development of SCLC. Abstract : The Tissue Factor Pathway Inhibitor‐2 inhibits small cell lung cancer growth Monitoring of small cell lung cancer growth in a mouse orthotopic model by imaging Increasing information on the role of TFPI‐2 in human lung tumour cells Increasing information on TFPI‐2 and protease expression in human tissue samples